Preparation of Hybrid Thiol‐Acrylate Emulsion‐Templated Porous Polymers by Interfacial Copolymerization of High Internal Phase Emulsions. Issue 9 (2nd March 2015) - Langford, Caitlin R.; Johnson, David W.; Cameron, Neil R.
<x xml:space="preserve">Abstract</x> Emulsion‐templated highly porous polymers (polyHIPEs), containing distinct regions differing in composition, morphology, and/or properties, are prepared by the simultaneous polymerization of two high internal phase emulsions (HIPEs) contained within the same mould. The HIPEs are placed together in the mould and subjected to thiol‐acrylate photopolymerization. The resulting polyHIPE material is found to contain two distinct semicircular regions, reflecting the composition of each HIPE. The original interface between the two emulsions becomes a copolymerized band between 100 and 300 μm wide, which is found to be mechanically robust. The separate polyHIPE layers are distinguished from one another by their differing average void diameter, chemical composition, and extent of contraction upon drying.